Kun̈ftige Wettbewerbsfaḧigkeit der Milchproduktion im Berggebiet Os̈terreichs und der Schweiz - Leopold Kirner; Christian Gazzarin (Agrarwirtschaft: Zeitschrift für Betriebswirtschaft, Marktforschung und Agrarpolitik, 2007)
– The mountain areas of Austria and Switzerland are important locations for dairy farming. Owing to natural conditions, the milk in these areas is produced at a considerably higher cost. Nevertheless, structural change in the mountain areas of both countries proceeded at a lower pace than in the plain areas. Milk production in the mountain area of Austria was appreciably expanded. This paper presents a number of attempts to explain these regional shifts, analysing the competitiveness of the farms, as well as the alternatives outside of milk production in the mountain and plain areas of Austria and Switzerland. In addition, we investigate whether milk production in these regions is also capable of holding its ground under future conditions. The on-average lower opportunity costs for land and labour in mountain areas are largely responsible for the high perseverance of dairy farmers in these regions. Common to both countries, however, is the fact that the competitiveness of farms in mountain areas can only be guaranteed by high direct payments. The extent of these direct payments is appreciably higher in Switzerland than in Austria, owing to the expected alignment of Swiss and EU milk prices, and the higher wage level in Switzerland. The high national economic importance of mountain milk production with regard to tourism and decentralised settlement explains the broad social acceptance of these payments, which should be less affected by cutbacks than other agricultural subsidies.
Keywords: 330; Milchviehhaltung; Internationaler Wettbewerb; Gebirge; Opportunitätskosten; Österreich; Schweiz